Study of Affecting Factors of Meteorological Parameters on Solar Radiation on Pokhara - Shrestha, Prakash M.; Regmi, Jeevan; Joshi, Usha; Poudyal, Khem N.; Chapagain, Narayan P.; Karki, Indra B. (Himalayan Physics, 2020)
Solar radiation data are of great signiﬁcance for solar energy systems. This study aimed to estimate monthly and seasonal average of daily global solar radiation on a horizontal surface in Pokhara (Lat.:28.21o N, Long.: 84o E and alt. 827 m above sea level), Nepal, by using CMP6 pyranometer in 2015. As a result of this measurement, monthly and yearly mean solar radiation values were 20.37 ±5.62 MJ/m2/ day in May, 11.37 ± 2.38 MJ/m2/ day in December and 16.82 ±5.24 MJ/m2/ day respectively. Annual average of clearness index and extinction coefficient are 0.51±0.14 and 0.53±0.31 respectively. There is positive correlation of maximum temperature and negative correlation of with global solar radiation.